Effects of sublingual immunotherapy for Dermatophagoides farinae on Th17 cells and CD4+CD25+ regulatory T cells in peripheral blood of children with allergic asthma. Issue 5 (3rd March 2014) - Tian, Man; Wang, Yu; Lu, Yueqing; Jiang, Yan‐he; Zhao, De‐yu
<x xml:space="preserve">Abstract</x> Background Sublingual immunotherapy is becoming a more common treatment for allergic diseases, particularly in pediatric clinics. This type of treatment is highly effective for Dermatophagoides farinae allergy, but the mechanisms resulting in immune tolerance have not been investigated. We explored the effects of sublingual immunotherapy with D. farinae drops on populations of subsets of T immune cells, specifically Th17 cells and CD4+CD25+ regulatory T cells (Treg cells), in peripheral blood of children with allergic asthma. Methods We assessed immune cell populations in 60 patients allergic to D. farinae who were randomly divided into 2 groups: a treatment group (n = 30) and a control group (n = 30), treated with sublingual administration of D. farinae drops or placebo, respectively, for 48 weeks. Clinical symptoms of asthma were scored for each individual before and after treatment, and the percentages of Th17 cells and CD4+CD25+ Treg cells in the peripheral blood were evaluated by flow cytometry at 12‐week intervals beginning at baseline. Results Both the mean daily symptom scores and percentages of Th17 cells significantly declined in the treatment group throughout the study period (p < 0.05), and in the control group both declined but without significant differences between time points. In contrast, the percentages of Treg cells significantly increased in the treatment group throughout the study period (p < 0.05), but no statistical difference was observed among different sampling times. Conclusion Sublingual administration of D. farinae drops alters T immune cell profiles and reduces asthma symptoms, likely resulting in enhanced immunosuppression in children with asthma.